Eine neue Spezies der Gattung Alytana Shaffer & Munroe, 2007 aus dem Oman (Dhofar) (Lepidoptera: Crambidae, Spilomelinae) - M. Seizmair (SHILAP, 2019)
Alytana bifurcalis Seizmair, sp. n. is described as new for Science. The adult male and female, and the genitalia are described and figured. The differential features as to the only hitherto known, Alytana aldabralis (Viette, 1958) are given. The occurrence of the genus Alytana Shaffer & Munroe, 2007 is new to the entomofauna of the Arabian Peninsula.